2006
DOI: 10.1016/j.jct.2005.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Vapour pressures of n-hexane determined by comparative ebulliometry

Abstract: The vapour pressures of n-hexane have been measured using comparative ebulliometry with water as the reference fluid. The measurements cover the temperature and pressure range (315.7 K, 41.1 kPa) to (504.0 K, 2876.8 kPa) and join smoothly with results selected from the literature to provide consistent results down to (289.7 K, 13.8 kPa). The combined data set have been described by a Wagner style equation with a fractional standard deviation of 4.2 AE 10 À5 in the vapour pressure. The critical pressure p c was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Table shows the values obtained with the automatic system described, every 2 kPa as indicated in section 2.2. Figure a shows the differences between the new experimental values and those from literature. , It can be observed that the greatest differences correspond with data published by Sauermann, for hexane higher than 1% in the interval T < 380 K.…”
Section: Presentation Of Results and Modelingsupporting
confidence: 54%
“…Table shows the values obtained with the automatic system described, every 2 kPa as indicated in section 2.2. Figure a shows the differences between the new experimental values and those from literature. , It can be observed that the greatest differences correspond with data published by Sauermann, for hexane higher than 1% in the interval T < 380 K.…”
Section: Presentation Of Results and Modelingsupporting
confidence: 54%
“…( 28)+Eq. (23) or E.q.(48)+Eq. (47), are still robust in a region close to the critical point (𝑇 𝑟 → 0.999) and in a low temperature range, 𝑇 𝑟 → 0.1.…”
Section: Discussionmentioning
confidence: 99%
“…59) with analytical volume expressions, and points are experimental data. The data sources: Ar, [18]; Methane, [21]; Ethane, [19]; n-Butane, [22]; cyclohexane, [26]; n-Hexane, [23]; n-Heptane, [26]; Benzene [27].…”
Section: Analytically Expressions For Thermodynamic Propertiesmentioning
confidence: 99%
“…41) with analytical volume expressions, and points are experimental data. The data sources: Ar, [13]; Methane, [16]; Ethane, [14]; n-Butane, [17]; cyclohexane, [19,20]; n-Hexane, [18]; n-Heptane, [21]; Benzene, [22].…”
Section: The Analytical Solution To the Vle Problem With The Srk Eosmentioning
confidence: 99%